2011
DOI: 10.1111/j.1475-3588.2010.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of stimulant treatment responders, partial responders and non-responders using objective measures in children and adolescents with hyperkinetic disorder

Abstract: Background: The aim of this study was to evaluate stimulant medication response following a single dose of methylphenidate (MPH) in children and young people with hyperkinetic disorder using infrared motion analysis combined with a continuous performance task (QbTest system) as objective measures. The hypothesis was put forward that a moderate testdose of stimulant medication could determine a robust treatment response, partial response and non-response in relation to activity, attention and impulse control me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…Because ADHD rating forms are vulnerable to placebo (Waschbusch et al 2009) and source (Gomez et al 2003) effects, the inclusion of objective test measures in clinical trials has been recommended by several authors (Teicher et al 2008;Waschbusch et al 2009;Sumner et al 2010). Computer-based continuous performance tests (cb-CPT) are a large family of laboratory tests measuring attention; they are administered in a diversity of forms.…”
Section: Introductionmentioning
confidence: 99%
“…Because ADHD rating forms are vulnerable to placebo (Waschbusch et al 2009) and source (Gomez et al 2003) effects, the inclusion of objective test measures in clinical trials has been recommended by several authors (Teicher et al 2008;Waschbusch et al 2009;Sumner et al 2010). Computer-based continuous performance tests (cb-CPT) are a large family of laboratory tests measuring attention; they are administered in a diversity of forms.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a CPT is a computer based programme which involves rapid presentation of visual or auditory stimuli where participants are asked to respond when a given target occurs but remain passive to non-targets. CPTs are a popular adjunct in the assessment of attention [24,25].…”
Section: A Snappyapp: Continuous Performance Testmentioning
confidence: 99%
“…More recently, psychometric tests are used in the assessment process to provide objective measures of patient's symptoms. Such measures of cognitive function also offer the potential to objectively measure response to medication, and could potentially hasten the process of treatment optimisation [10].…”
mentioning
confidence: 99%
“…This CPT is preferable to using the X-CPT in adults where ceiling effects are often found [2]. These kinds of objective tests are commonly used to assess attention [10] and are considered to be the most sensitive assessment of medication effects [12]. Studies have shown a clear separation on CPTs between people with ADHD and controls, with ADHD participants showing poorer performance on measures of attention and impulsivity [13,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation